Advancing Parkinson’s disease research in Africa: a strategic training framework of the global Parkinson’s genetics program - Step, Kathryn; Eltaraifee, Esraa; Elsayed, Inas; Rasaholiarison, Nomena; Okubadejo, Njideka Ulunma; Walker, Richard; Mohamed, Wael Mohamed Yousef; Rizig, Mie; Bandres-Ciga, Sara; Noyce, Alastair J.; Dey, Sumit; Bardien, Soraya; et al. (John Wiley and Sons Inc, 2025)
Parkinson’s disease (PD) is a neurodegenerative disorder with diverse motor, nonmotor, and neuropsychiatric symptoms. Genetic and environmental factors contribute to its development.1 However, PD research has predominantly focused on individuals of European descent, with over 80% of genome-wide association studies (GWAS) centered on this group.2 This lack of diversity limits our understanding of disease mechanisms and creates disparities, preventing the equitable implementation of personalized medicine.2-4 Collaborative efforts are underway to enhance diversity in PD genetic research. Africa is the second most populous continent and is expected to host 26% of the global population by 2050.5 Despite exhibiting the highest genetic variation and complex admixture, African populations are significantly underrepresented in PD research, with only a fraction of their extensive genetic diversity being surveyed,6 primarily focusing on Mendelian genes associated with monogenic PD.2,7,8 Genetic studies have characterized a limited number of Africa’s 2000 ethnolinguistic groups, mainly using genotyping arrays with variants common in Europeans, leaving the distribution of novel, rare, and medically relevant variations largely unknown.8 For instance, although the LRRK2 p.G2019S variant is present in 1% to2% of Europeans PD patients,9 29.7% of familial Ashkenazi Jewish PD patients,10 and 40% of North African Arabs,11 it has not been identified in Black Africans to date.12 Given Africa’s ethnic and genetic diversity, including these populations is crucial for understanding novel genetic determinants underlying PD risk, onset, and progression.13 Research capacity and research infrastructure in Africa remain limited, with PD genetic research facing challenges, including political and economic instability, a predominant focus on infectious diseases, limited medical personnel, and insufficient funds and infrastructure.